Assessment of health and wellness centres in hilly district of Himachal Pradesh - Sood, Abhilash; Kumar, Devender; Kumar, Arvind; ., Sanjay; Sood, Aditya; ., Neetu (International Journal Of Community Medicine And Public Health, 2021)
Background: The National health policy 2017 has envisioned Health and wellness centres under Ayushman Bharat in health care system of India. In Himachal Pradesh with significant geographical disparities and challenges, establishment of HWC in far-flung areas indicates a paradigm shift in government policy in addressing health-care needs through primary health-care setup. The aim of the study was conducted to identify the gaps in Ayushman Bharat Health and wellness centres under various domains of service delivery. Methods:A cross-sectional study was conducted to assess the AB-Health and wellness centres in district Hamirpur of Himachal Pradesh. Duration of study was five months with effect from 1st March 2021 to 31st July 2021.Study tool used was a validated checklist prepared by National Health Mission Government of Himachal Pradesh. Results: There is deficient human resource in Health and wellness centres (PHCs and SCs). Inadequate skill competencies observed especially in newly appointed health care workers. Equipment for telemedicine are available at each health centre but none or very few tele-consultation are being done by health care workers. Conclusions:In present study it was seen that target to upgrade AB-HWCs have been achieved but still human resource, infrastructure, trainings, skill competencies of health care workers are inadequate. To fill up these gaps there is need of focussed and target oriented determination by health department of state.